Construction technology and intelligent application of transparent working face model - Xiaohui WANG; Zaibin LIU; Baohui CHEN; Liang MA; Yaoquan GAO; Dongliang ZHANG; Yiming DU; Xiaorong LEI; Junsheng YAN (Meitan kexue jishu)
The working face model is an important prerequisite for guiding safe and efficient production in coal mines and holds significant importance for achieving precise coal mining and geological security. Especially under complex geological conditions, if the working face model cannot accurately describe the relationships between geological structures and strata, it will impact the planning of mining areas, mining and excavation processes, and production efficiency. Taking the working face of a mine under complex geological conditions as an example, this study conducts research on high-precision working face modeling technology and its intelligent application. First, a construction technology for strata and faults is proposed, successfully solving the challenges of special geological phenomena and the three-dimensional spatial recalculation of reverse faults. Additionally, dynamic updating technology is introduced to achieve local dynamic corrections of the model, significantly improving its accuracy and practicality. Secondly, by integrating real-time monitoring data, intelligent planning for cutting and intelligent geological prediction technologies are proposed, which effectively enhance the precision and timeliness of production decision-making. Subsequently, a static model of the I030903 working face was constructed, incorporating local dynamic updating capabilities. This dynamic model was applied to the transparent geological security system for coal mines, achieving significant application results. The results indicate that the modeling technology can quickly and accurately simulate any complex geological body, providing convenience for handling issues such as stratigraphic unconformities, strata pinching out, coal seam bifurcation, and fault cutting. Verified data show that model errors are within 0.2 m, with 97% of errors falling within the 0-0.1 m range. The intelligent cutting planning technology, based on the transparent working face model, effectively guided the precise coal extraction by the shearer, while the intelligent geological prediction technology could automatically generate warning information in abnormal situations and promptly communicate it to relevant personnel. The research results demonstrate the advancement and feasibility of this method, providing solid technical support and assurance for intelligent coal mining.